Study on the changes of miRNAs and their target genes in regulating anthocyanin synthesis during purple discoloration of cauliflower curd under low temperature stress - Yao, Xingwei; Zhang, Qi; Chen, Haidong; Ge, Xianhong; Guo, Yangdong; Chen, Daozong (Frontiers in Plant Science, 2024)
Cauliflower is widely cultivated all over the world is attributed to its palatable flavor, high levels of anti-cancer compounds, and diverse array of nutrients. Exposure to extremely cold stress during production can result in a more frequent occurrence of purple discoloration in cauliflower curds. In response to cold stress, plants naturally produce anthocyanins to eliminate reactive oxygen species (ROS) generated as a defense mechanism. This research involved conducting mRNA sequencing analysis on cauliflower curds both before and after exposure to cold stress treatment. It was determined that the up-regulation of anthocyanin biosynthesis-related genes CHS, CHI, DFR, ANS, UGFT, PAP1/2, and MYBL2 occurred significantly in response to cold stress, resulting in a significant increase in total anthocyanin content. Subsequently, miRNA sequencing was employed to identify miRNAs in cauliflower curds, followed by differential expression analysis. The results showed that Bna-miR289 and Ath-miR157a may play a key role in regulating the accumulation of anthocyanin in cauliflower curds. Furthermore, we utilized degradome sequencing data to predict the target genes of the identified miRNAs, resulting in the identification of BolK_3g48940.1, BolK_9g11680.1, BolK_7g41780.1, BolK_3g68050.1, and BolK_3g72970.1 as targets. Subsequently, the expression patterns of the miRNAs and their target genes were validated using qRT-PCR, the results showed that Ath-miR157a and its target genes BolK_3g68050.1 and BolK_3g72970.1 may be the key to the purple of cauliflower curds under cold stress. Our preliminary findings identified key miRNAs and their target genes that may be involved in regulating anthocyanin synthesis, thereby enhancing the cold tolerance of cauliflower through mRNA, miRNA, and degradome sequencing. Overall, our study sheds light on the activation of anthocyanin synthesis in flower curds under cold stress conditions as a mechanism to enhance resilience to adverse environmental conditions.